Risk factors with high blood pressure in the adult population of Kang ( Kgalagadi North ), Botswana - Tshitenga, S. (University of Limpopo (Medunsa Campus), 2010)
Background: The state of Hypertension disease is universally under diagnosed and/or inadequately treated resulting in extensive target-organ damage and premature deaths. Therefore, sustainable and aggressive population-based programs for hypertension awareness, prevention, treatment, and control are keys of success in limiting this epidemic. The study aims to determine the Kang Adult population’s hypertension prevalence and the relationship between high blood pressure, anthropometric measures and their life style factors such as diet, use of tobacco products and alcohol consuming habits. Methodology: The study, a population based cross-sectional trial, was conducted on adult residents of Kang (18 year-old and above) from November to December 2008. Data was collected using the questionnaire, through physical measurements of weight, height and BP using a modified protocol based on World Health Organization (WHO) STEP wise instruments on chronic disease (Bonita, 2001). The sample consisted of 161 participants between 20 and 82 years of age. Results: Hypertension was observed in 31.6% of participants (95% CI: 24.6%-39.5%). With regard to the hypertension prevalence rate, no significant differences were observed between males and females (males 28.3% versus females 33.6%, p = 0.59). An elevated blood pressure was seen with significantly higher frequency in overweight group compared with the normal weight group (p = 0.029), in obese group compared x with the normal weight group (p = 0.002), and in obese group compared with the overweight group (p = 0.045). The study found no significant association between hypertension and use of tobacco products (p=0.46) or alcohol consumption (p=0.73), went in vigorous-intensity activity (p=0.22) and moderate-intensity activity that causes large increases in breathing, or heart rate for at least 10 minutes continuously (p=0.70). Conclusions: It is concluded that hypertension is a common problem in adult Kang population, with a prevalence of 31.6%. Hypertension prevalence was found to be associated with anthropometric measurements such as overweight and obesity. No significant association between hypertension and use of tobacco products, alcohol consumption, vigorous-intensity and moderate-intensity activities that cause increases in breathing or heart rate for at least 10 minutes continuously. However, the present study had the limitation of a small sample size. Further studies are needed to clarify the hypertension magnitude throughout the country, with large samples.
Thesis (M Med (Family Medicine))--University of Limpopo, 2010.
Keywords: Hypertension; Blood pressure